RELEVANSI SUSTAINABILITY, ACCOUNTABILITY, TRANSPARENCY PROGRAM ENTREPRENEURIAL UNIVERSITY TERHADAP SIKAP KOMUNITAS GEREJA - Ayu Dwidyah Rini (Universitas Brawijaya, 2015)
Abstrak: Relevansi Sustainability, Accountability, Transparency Program Entrepreneurial University terhadap Sikap Komunitas Gereja. Penelitian ini bertujuan mengkaji hubungan antara sustainability, akuntabilitas dan transparansi dalam implementasi CSR terhadap sikap kognitif, afektif dan konatif komunitas penerima program pelatihan kewirausahaan. Melalui pendekatan kuantitatif dengan teknik analisis regresi multipel, ditemukan bahwa terjadi hubungan yang positif dari sustainability, accountability dan transparency terhadap sikap komunitas pada program pelatihan kewirausahaan jemaat GKJW Mutersari Mojowarno. Kegiatan Corporate Social Responsibility akan mampu meningkatkan hubungan baik antara unversitas dan masyarakat sehingga mampu pula meningkatkan citra positif universitas. Abstract: Relevance of Sustainability, Accountability, Transparency toward Attitude of Church Community in Entrepreneurial University Program. The purpose of this research is to identify the relationship of continuity, accountability, and transparency in the CSR Implementation toward cognitive, affective, and conative attitude of community in Entrepreneurial Training Program. The object of the research was the church’s community (GKJW) in Mutersari Mojowarno Jombang. By employing quantitative approach using multiple linear regression as data analysis technique, it is found that that there is significant relationship among variables in this research. Corporate Social Responsibility activities will enhance the relation between university and community and in turn improve the university image publicly.